Micellar liquid chromatographic determination of sertaconazole and terconazole in bulk, pharmaceutical dosage forms and spiked human plasma - Mohamed Rizk; Safaa S. Toubar; Maha M.A. El-Alamin; Marwa M.M. Azab (Faculty of Pharmacy, Cairo University, 2014)
A micellar liquid chromatographic method was developed for the determination of sertaconazole and terconazole in bulk, dosage forms and human plasma using intersil cyano column and mobile phase consisting of 0.1 M sodium dodecyl sulphate, 20% 1-propanol, and 0.3% triethylamine in 0.02 M ortho-phosphoric acid (pH 4) at 225 nm. Different chromatographic parameters were studied, e.g. types of columns, pH of mobile phase, concentration of sodium dodecyl sulphate, 1-propanol, triethylamine, etc. The method was validated over the concentration ranges 8-40 and 16-80 μg/ml, for sertaconazole and terconazole, respectively. The method was sensitive with limits of detection of 1.24 and 1.67 μg/ml for sertaconazole and terconazole in bulk, respectively. Inter and intra-day results showed % RSD < 0.9% and 1.55% for sertaconazole and terconazole, respectively. The result obtained by the proposed method was compared with that obtained by the reference HPLC technique. Furthermore, the proposed method was successfully applied as a stability-indicating method for the determination of drugs under different stressed conditions. The method showed good selectivity, repeatability, linearity and sensitivity according to the evaluation of the validation parameters.